Understanding and predicting forming quality of copper in incremental sheet forming: forming forces, material properties, and geometric deviation - Kai Han; Xiaoqiang Li; Yanle Li; Jinxin Zang; Junzhou Chen (Journal of Materials Research and Technology)
The influence mechanisms on forming quality in incremental sheet forming (ISF) remain inadequately elucidated, which significantly restricts the quality prediction accuracy and hinders widespread industrial application of ISF process. This study employs an integrated experimental and numerical approach to elucidate material deformation mechanisms during ISF, with focus on forming forces, mechanical properties, and geometric deviations. The specific deformation paths involving bending-reverse bending combined with loading-unloading critically influences forming force prediction accuracy. Implementation of the Yoshida-Uemori combined hardening constitutive model enables high-precision forming force prediction with errors below 6.8 %. Additionally, the study demonstrates that the Bauschinger effect induced by reverse loading during ISF leads to significant material softening, with simulation predictions based on the Yoshida-Uemori constitutive model showing less than 3.2 % error compared to experimental data. Furthermore, a theoretical analytical model for geometric deviation considering the deformation process was established, confirming that the elastic bending moment generated during bending-reverse bending processes is the primary cause of geometric deviations, with prediction errors controlled within 24.8 %. This research elucidates the key influence mechanisms on ISF quality and achieves precise prediction of the forming process, laying a theoretical foundation for the industrialization of ISF technology.